2016
DOI: 10.1007/s10549-016-3876-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and pathological gene fusions in breast cancer: current advances in genomic discovery and clinical implications

Abstract: Gene fusions have long been considered principally as the oncogenic events of hematologic malignancies, but have recently gained wide attention in solid tumors due to several milestone discoveries and the advancement of deep sequencing technologies. With the progress in deep sequencing studies of breast cancer transcriptomes and genomes, the discovery of recurrent and pathological gene fusions in breast cancer is on the focus. Recently, driven by new deep sequencing studies, several recurrent or pathological g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 83 publications
0
48
0
1
Order By: Relevance
“…The criteria for selecting the articles were as follows: (1) Results reported about a case-control study, study published as an original study evaluating the association between PIN3 16-bp duplication polymorphism of TP53 and the risk of breast cancer; (2) No deviation from Hardy-Weinberg Equilibrium (HWE) in controls; (3) No in uence on the pooled odds ratio (OR) and p-values ( Figure 1); and (4) Full text available. Two investigators independently reviewed the abstracts of the initial search and assessed each article for inclusion in the meta-analysis.…”
Section: Article Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for selecting the articles were as follows: (1) Results reported about a case-control study, study published as an original study evaluating the association between PIN3 16-bp duplication polymorphism of TP53 and the risk of breast cancer; (2) No deviation from Hardy-Weinberg Equilibrium (HWE) in controls; (3) No in uence on the pooled odds ratio (OR) and p-values ( Figure 1); and (4) Full text available. Two investigators independently reviewed the abstracts of the initial search and assessed each article for inclusion in the meta-analysis.…”
Section: Article Inclusion Criteriamentioning
confidence: 99%
“…With the advent of genomics, dramatic advances have been made in breast cancer research. Recent report showed that in addition to clinical, lifestyle and environmental risk factors, an individual's genetic background plays a crucial role in the development of breast cancer [3]. Several genes have been shown to be associated with an increased risk of breast cancer, such as damaged DNA repair genes (BRCA1 and BRCA2), tumor protein p53 (TP53), Checkpoint kinase 2 (CHEK2), methylenetetrahydrofolate reductase (MTHFR), broblast growth factor receptor 2 (FGFR2) and glutathione S-transferase mu 1 (GSTM1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in the literature that some of these fusion pairs are known to be the recurrent gene fusions detected in Breast Invasive Carcinoma. For example: ESR|CCDC170 and EXTL3|SARAF are known recurrent gene fusion pairs detected in breast invasive carcinoma (Veeraraghavan, Ma, Hu, & Wang, 2016; Yoshihara et al, 2015). …”
Section: Basic Protocol 2: Scaling Analysis On the Cgc Platform With mentioning
confidence: 99%
“…Many of the gene fusions detected are known recurrent gene fusions in breast cancer. For example, the ESR|CCDC170 gene fusion is a known recurrent gene fusion transcript in breast invasive carcinoma (Veeraraghavan et al, 2016). …”
Section: Figurementioning
confidence: 99%
“…Unfortunately RNA-seq shows computational criticalities in SNV/INDELs detection, such as those due to splicing [2] and the need of statistical models that are insensitive to variability in read coverage due to unequal transcript expression levels [3–5]. RNA-seq has been also used for the detection of translocations generating functional aberrant proteins (also known as chimeras or fusion transcripts [6]), which could act as driver mutations in cancer [7, 8]. Indeed, the sequencing coverage required for fusion transcripts detection in RNA-seq is much lower than the one needed for Whole Genome Sequencing (WGS) making the RNA-seq a suitable methodology for fusion detection.…”
Section: Introductionmentioning
confidence: 99%